Preliminary study using on-field methods for ketosis detection in goats - Ahmad Affandi, Syahirah; Mohd Azmi, Amirul Faiz; Abu Hassim, Hasliza; Saharee, Abdul Aziz; Mansor, Rozaihan (2015)
Ketosis is a common metabolic problem that occurs as a result of negative energy balance due to inadequate feeding. Early detection is important to prevent losses from treatment cost and death of the dam and fetus. Little information is available on the diagnosis of ketosis in goats and in Malaysia, no studies have been conducted to date. A preliminary study was conducted among goat populations in two adopted farms of Faculty of Veterinary Medicine, Universiti Putra Malaysia, Serdang, Malaysia located in Negeri Sembilan, Malaysia to investigate the presence of ketone bodies in goats at risk. Based on the observation (n=10), most of the does were thin with body condition score 2.5 out of 5. None of the does showed any clinical signs of ketosis except for depression. The human hand-held ketometer, Freestyle™ Precision Xtra (FSPX; Abbot Germany, Wiesbaden, Germany) and a cow-side ketone powder, KetoCheck™ powder (KCP; Ceva Animal Health, USA) were used on-field. FSPX produces a quantitative result of the blood β-hydroxybutyrate (BHBA) concentration while KCP is a qualitative method to detect ketone bodies (e.g acetoacetate acid (AceAc) in the plasma, urine or milk sample. In this study, 2/10 and 1/10 animals were found positive for ketosis with detection using FSPX and KCP respectively.